Daily uplifts, well-being and performance in organizational settings: the differential mediating roles of affect and work engagement - Junça-Silva, A.; Caetano, A.; Lopes, R. R. (Journal of Happiness Studies, 2017)
Affective events theory suggests that affective events at work arouse emotional reactions that influence employees’ attitudes and behaviour in the workplace. In the present study, we apply this theoretical framework to clarify the interplay of variables that explain well-being and performance. We analysed the mediating role of positive affect and work engagement between daily uplifts and well-being, and between daily uplifts and performance. Results from a sample of 293 employees revealed that daily uplifts were positively associated with well-being and performance. While the effects of daily uplifts on wellbeing were fully mediated by positive affect and work engagement, the effects of daily uplifts on performance were only partially mediated by positive affect and work engagement. In both cases, the effect of positive affect was bigger than that of work engagement. The relations explored provide new theoretical elements for models that explain which variables influence well-being and performance in organizational contexts. The implications for employee health and organizational success are discussed.